2016
DOI: 10.1016/j.bbamcr.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome biogenesis, protein targeting mechanisms and PEX gene functions in plants

Abstract: Peroxisomes play diverse and important roles in plants. The functions of peroxisomes are dependent upon their steady state protein composition which in turn reflects the balance of formation and turnover of the organelle. Protein import and turnover of constituent peroxisomal proteins are controlled by the state of cell growth and environment. The evolutionary origin of the peroxisome and the role of the endoplasmic reticulum in peroxisome biogenesis are discussed, as informed by studies of the trafficking of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 131 publications
0
62
0
Order By: Relevance
“…This involves cleaving PTS2 and the collaboration of a battery of proteins called peroxins (PEXs) which are peroxisomal biogenesis factors encoded by PEX genes involved in matrix protein transport through PTS1 and PTS2 pathways. They are located in both the cytosol and peroxisomal membrane [34].…”
Section: Introductionmentioning
confidence: 99%
“…This involves cleaving PTS2 and the collaboration of a battery of proteins called peroxins (PEXs) which are peroxisomal biogenesis factors encoded by PEX genes involved in matrix protein transport through PTS1 and PTS2 pathways. They are located in both the cytosol and peroxisomal membrane [34].…”
Section: Introductionmentioning
confidence: 99%
“…1; reviewed in 1, 5]. Peroxisomal membrane proteins (PMPs) can be recognized by PEX19, a receptor that docks with PEX3 in the membrane to allow PMP insertion (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since all peroxisomal proteins are encoded in the nucleus, they need to be imported into peroxisomes from the cytosol through a process mediated by peroxins (or PEX proteins), most of which are conserved across kingdoms (Hu et al, 2012;Cross et al, 2016). Recent molecular genetic studies have shed light on the function of plant PEX proteins and revealed regulatory mechanisms.…”
Section: Peroxisome Protein Import and Proliferation/divisionmentioning
confidence: 99%